Phillips in retrospect - David Laidler (The University of Western Ontario, Department of Economics, 2001)
[A Review Essay on A. W. H. Phillips ...] Historians of economic thought know that citation counts are a very imperfect measure of an economist's influence. Imagine, for example, what Ricardo's might look like were he cited every time someone mentioned comparative advantage, or Walras' were he cited every time anyone mentioned general equilibrium, or indeed on a smaller scale, what Bill Phillips' own count might look like had he written up the adaptive expectations idea and published it in a journal, instead of simply passing it on to Friedman and Cagan. Even so, Phillips' personality mixed creativity and unselfish modesty in such an unusually high ratio that his contributions have long needed a little help to find their proper and important place in the history of our sometimes unpleasantly competitive subject. It is as fortunate as it is just that his work has found a capable and dedicated advocate in Robert Leeson. We are all in his debt for this volume.
Keywords: 330; Dogmengeschichte; Theorie